Educação científica : um estudo sobre a iniciação científica em universidades do Comung - Rocha, Aline (2008)
The present dissertation mentions the importance to it of the presence of the scientific education in the materializes communitarian university by means of the scientific initiation. Such subject was chosen by perceiving the influence of the world globalize in the higher education, and understanding themselves and giving credit that the scientific education can be to differential in the hegher education. This study was carried out next to scholarship holders and ex scholarship holders of scientific initiation in three institutions of communal education of the interior of the state of RS linked to the Consortium of the Communal Universities Gaúchas (Comung). For the collection of data, beyond documentary research was utilized like instrument a questionnaire sent e-mail with subjective and objective questions, by means of the which was possible analyze qualitative and quantitative data. Initially the study presents information about the segment of the communal institutions linked to the Consortium of the Communal Universities Gaúchas, and, also the panorama of the research in these institutions. Subsequently, they were brought questions about the university and to research related to the higher education in a world globalized. Also, it does a reflection about the scientific education that the student acquires scholarship holders while of initiation. Still, if it presents the results of the research that analyzed the profile of scholarship holders and ex-scholarship of scientific initiation, beyond verify his knowledge about science, and its importance in the world. With this study established itself that the scientific education through the scientific initiation comes being employed in the IES of the Comung.